Vulnerable road users and the coming wave of automated vehicles: Expert perspectives. (March 2021) - Tabone, Wilbert; de Winter, Joost; Ackermann, Claudia; Bärgman, Jonas; Baumann, Martin; Deb, Shuchisnigdha; Emmenegger, Colleen; Habibovic, Azra; Hagenzieker, Marjan; Hancock, P.A.; Happee, Riender; Krems, Josef; et al.
Highlights: Researchers provided their views on the future of AV-VRU interaction. They noted that fully autonomous vehicles will not be introduced any time soon. Smart infrastructure and traffic segregation were regarded as crucial but costly. eHMIs were seen as vital, but instructions, surface anthropomorphism, and text were rejected. AR was regarded as promising, but implicit cues were believed to remain dominant. Abstract: Automated driving research over the past decades has mostly focused on highway environments. Recent technological developments have drawn researchers and manufacturers to look ahead at introducing automated driving in cities. The current position paper examines this challenge from the viewpoint of scientific experts. Sixteen Human Factors researchers were interviewed about their personal perspectives on automated vehicles (AVs) and the interaction with VRUs in the future urban environment. Aspects such as smart infrastructure, external human-machine interfaces (eHMIs), and the potential of augmented reality (AR) were addressed during the interviews. The interviews showed that the researchers believed that fully autonomous vehicles will not be introduced in the coming decades and that intermediate levels of automation, specific AV services, or shared control will be used instead. The researchers foresaw a large role of smart infrastructure and expressed a need for AV-VRU segregation, but were concerned about corresponding costs and maintenance requirements. The majority indicated that eHMIs will enhance future AV-VRU interaction, but they noted that implicit communication will remain dominant and advised against text-based and instructive eHMIs. AR was commended for its potential in assisting VRUs, but given the technological challenges, its use, for the time being, was believed to be limited to scientific experiments. The present expert perspectives may be instrumental to various stakeholders and researchers concerned with the relationship between VRUs and AVs in future urban traffic.